IDENTIFIKASI JENIS-JENIS AEROPLANKTON SEBAGAI DASAR PARAMETER KUALITAS UDARA DI WILAYAH PEKANBARU - Ramadansur, Rahmat; Dinata, Marta; Sembiring, Al Khudri; Firda, Arlian; Martalasari, Martalasari; Ningrum, Gina Fitria (Universitas Lancang Kuning, 2024)
This research aims to identify types of aeroplankton as air quality parameters in the Pekanbaru area. Aeroplankton samples were collected using the Purposive Sampling method where samples were taken 1x24 hours for 20 days in 2 different sub-districts, namely Sukajadi District and Tenayan Raya District. Identification and counting of aeroplankton is carried out in the laboratory. The results showed that the abundance of aeroplankton in Sukajadi subdistrict was higher than in Tenayan Raya subdistrict. In both sub-districts, the abundance of aeroplankton is dominated by the phytoplankton and zooplankton groups. Where aeroplankton can be the basis for air quality parameters in the two sub-districts.